2013
DOI: 10.1016/j.urolonc.2012.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific membrane antigen-based imaging

Abstract: SUMMARY Prostate cancer (PC) is the most common non-cutaneous malignancy affecting men in North America. Despite significant efforts, conventional imaging of PC does not contribute to patient management as much as imaging performed for other common cancers. Given the lack of specificity in conventional imaging techniques, one possible solution is to screen for PC specific antigenic targets and generate agents able to specifically bind. Prostate specific membrane antigen (PSMA) is over-expressed in PC tissue, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 49 publications
2
81
0
12
Order By: Relevance
“…Studies have shown variable efficacy in PCa detection using ProstaScint, with average positive and negative predictive values of 60% and 70%, respectively [26]. However, this tracer binds to the intracellular domain of PSMA and thereby detects only necrotic tissue, having limited ability to detect viable cancer, including bone metastasis, giving it a high false-negative rate and limited applicability in the setting of recurrent disease [27].…”
Section: Imagingmentioning
confidence: 99%
“…Studies have shown variable efficacy in PCa detection using ProstaScint, with average positive and negative predictive values of 60% and 70%, respectively [26]. However, this tracer binds to the intracellular domain of PSMA and thereby detects only necrotic tissue, having limited ability to detect viable cancer, including bone metastasis, giving it a high false-negative rate and limited applicability in the setting of recurrent disease [27].…”
Section: Imagingmentioning
confidence: 99%
“…However, their application is most valuable in late-stage, recurrent, or metastatic PCa. Increasing efforts are being made in developing PET imaging agents targeting specific biomarkers of PCa, such as gastrin-releasing peptide receptor (GRPR) (5) and prostate-specific membrane antigen (6).…”
mentioning
confidence: 99%
“…Для стадии Т 2 диагностическая точ-ность нативной МРТ составляет не более 58%. Кроме того, методы анатомической визуализации (КТ, МРТ, МР-спектроскопия) имеют низкую чувствительность и специфичность при обнаружении метастатического РПЖ с метастазами в лимфатические узлы и другие мягкие ор-ганы и ткани [1,5,11].…”
Section: анатомическая визуализацияunclassified
“…В отличие от ПСА, ПСМА не обнаруживается в крови. Таким образом, ПСМА является идеальным маркером клеток РПЖ и прекрасной целью для радионуклидной визуализации и терапии [11,13,15].…”
Section: простатспецифический мембранный антиген как кандидат в биомаunclassified